Local Drug Delivery Systems for Vital Pulp Therapy: A New Hope - Ardavan Parhizkar; Saeed Asgary (International Journal of Biomaterials)
Vital pulp therapy (VPT) is deliberated as an ultraconservative/minimally invasive approach for the conservation of vital pulpal tissues, preservation of dental structure, and maintenance of tooth function in the oral cavity. In VPT, following the exposure of the dental pulp, the environment is prepared for the possible healing and probable refunctionalisation of pulpal connective tissue. However, to succeed in VPT, specific biomaterials are used to cover and/or dress the exposed pulp, lower the inflammation, heal the dental pulp, provoke the remaining odontoblastic cells, and induce the formation of a hard tissue, i.e., the dentinal bridge. It can be assumed that if the employed biomaterial is transferred to the target site using a specially designed micro-/nanosized local drug delivery system (LDDS), the biomaterial would be placed in closer proximity to the connective tissue, may be released in a controlled and sustained pattern, could properly conserve the remaining dental pulp and might appropriately enhance hard-tissue formation. Furthermore, the loaded LDDS could help VPT modalities to be more ultraconservative and may minimise the manipulation of the tooth structure as well as pulpal tissue, which could, in turn, result in better VPT outcomes.